Letramentos e surdez : histórias de uma professora ouvinte no mundo dos surdos - Almeida, Judith Mara de Souza (2015)
The main objective for this thesis has been to narrate, describe and analyze my experience as a hearing-teacher teaching Portuguese to deaf students. My specific objectives are: to comprehend how this living experience has happened and its implications to the teaching-learning process, and, furthermore analyze the literacy practices in the experience. Related to these objectives, two questions led to the current study: what curriculum is built in this experience? Which types of literacy are present in the living experience? Studying the experience as my research object, this narrative inquiry is based on Connelly; Clandinin (1988, 1998, 1999, 2006), Clandinin; Connelly (1995, 2000, 2004, 2007, 2011) and Mello (2005, 2012) in the context of a Portuguese class in a special needs school for deaf students located in TrianguloMineiro, in the Brazilian state of Minas Gerais. Three deaf female students and I, as a teacher-researcher, were the participants of this study. Our interaction occurred mostly mediated by a professional interpreter. The field texts were composed from field notes, recorded video classes, diaries of recorded video classes which were transcribed by me, a video diary made by the participants and transcribed my me, teaching sequences purposed to our Portuguese classes and activities developed with students in the classroom. Theoretical studies which were the foundation for this thesis are mainly: Hutchinson (2010), Carmozine; Noronha (2012) and Luz (2013) based on a social-anthropological conception of deafness; Mantoan and Prietto (2005), Pimentel (2012), Crochík (2012), Martins (2012), Denari (2008), Mendes and Toyoda (2008) in the approach about inclusion through diversities front. Fox (2007) and Fernandes (2003) regarding to Libras (Brazilian Sign Language). In order to discuss literacy, the main references are the reseachers Mortatti (2006), Ferreiro (1991)and Freire (2001). Discussing about reading, the study is based on researchers as Kleiman (1989, 1999, 2004, 2007) and Rojo (2004). The studies about literacies are mainly based on researchers as Street (1995, 2012, 2014) and Cope e Kalantzis (2012). The approach about curriculum, our reference is the concepts presented by Schwab (1978), Connelly; Clandinin (1988) and Mello (2004, 2012). Moreover, Lugones (1978) based the discussion about curriculum from the perpective of arrogance. The study by Machado (2005) supports the conception of genres. The clarification about teaching sequences comes along theoretical references such as the studies by Dolz and Schneuwly (2004) and Cristóvão (2008). The analysis through meaning composition (Ely, Vinz, Downing, Anzul, 2001), enabled me to observe many tensions in the living experience between the hearing-teacher and deaf students.